STRATEGI FUNDRAISING LAZISMU KABUPATEN LUMAJANG UNTUK MELATIH GEMAR BERSEDEKAH PADA SISWA SMK MUHAMMADIYAH LUMAJANG - Aro fik; Muhammad Ali Mufti (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research was conducted because of the background that the fact of Indonesia being enveloped in widespread poverty, ignorance and a very low human development index.  As a country with the largest Muslim population in the world, Indonesia has a fairly high potential for zakat, infaq and almsgiving.The establishment of LAZISMU is intended as a institution with modern management to be part of solving social problems (problem solvers) of the community that continues to grow. The formulation of the problem from this research is First, how is the LAZISMU fundraising strategy of Lumajang Regency in increasing the collection of zakat, infaq and alms, secondly what the problem is faced by LAZISMU Lumajang in training students to like almsgiving, what are the three factors that cause students of SMK Muhammadiyah Lumajang to like almsgiving. This type of research was qualitative research with a descriptive qualitative approach that collects primary data through interviews from LAZISMU, principals, teachers and students of SMK Muhammadiyah Lumajang, there was a seconder data in can be obtained from the regular literature and documents of LAZISMU and SMK Muhammadiyah Lumajang, after all the data was collected in a decorative analysis and described in a descriptive form. The results of the study concluded that, first the fundraising strategy through the alms movement a thousand gives a positive response to the community and educational institutions so that students like to give alms, the obstacles faced are internal and external factors that are almost the same, students of SMK Muhammadiyah Lumajang like to give alms because of the first few things the  establishment of a system in  the second  school socialization from the third LAZISMU  good collaboration of the residents of  the fourth school  of the role model.Keywords: Fundraising Strategy , Hobby, Almsgiving. Penelitian ini dilakukan kerena dilatar belakangi bahwa fakta Indonesia yang berselimut dengan kemiskinan yang masih meluas, kebodohan dan indeks pembangunan manusia yang sangat rendah. Sebagai negara berpenduduk muslim terbesar di dunia, Indonesia memiliki potensi zakat, infaq dan sedekah yang terbilang cukup tinggi. Berdirinya LAZISMU dimaksudkan sebagai institusi pengelola zakat dengan manajemen modern yang dapat menghantarkan zakat menjadi bagian dari penyelesai masalah (problem solver) sosial masyarakat yang terus berkembang. Rumusan masalah dari penelitian ini adalah Pertama, bagaimana strategi fundraising LAZISMU Kabupaten Lumajang dalam meningkatkan pengumpulan zakat, infaq dan sedekah, kedua Kendala apa saja yang dihadapi LAZISMU Lumajang dalam melatih siswa gemar bersedekah, ketiga faktor-faktor apa saja yang menyebabkan siswa SMK Muhammadiyah Lumajang gemar bersedekah. Jenis penelitian ini adalah penelitian kualitatif dengan pendekatan kualitatif diskriptif yang menghimpun data primer melalui wawancara dari pihak  LAZISMU, kepala sekolah, Guru dan siswa SMK Muhammadiyah Lumajang, adapun data Skunder di dapat dari lieteratur dan dokumen LAZISMU dan SMK Muhammadiyah Lumajang, setelah semua data terkumpul di  lanjut analisis secara kulitatif dan diuraikan dalam bentuk diskriptif. Hasil dari penelitian menyimpulkan bahwa, pertama strategi fundraising melalui gerakan sedekah sehari seribu memberikan respon positif kepada masyarakat dan lembaga pendidikan sehingga siswa gemar bersedekah, kendala yang dihadapi adalah faktor internal dan external yang hampir sama, siswa SMK Muhammadiyah Lumajang gemar bersedekah karena beberapa hal pertama terbangunnya sistem di sekolah kedua sosialisasi dari LAZISMU ketiga kolaborasi warga sekolah keempat suri tauladan yang baik.Kata Kunci: Strategi Fundraising, Gemar, Sedekah